2022
DOI: 10.3390/ijerph19041928
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Dementia Knowledge and Attitudes among the Youth and Older Adults: Insights from the Construal Level Theory Perspective

Abstract: Based on Construal Level Theory (CLT), the youth and older adults have different psychological distances towards dementia that may lead to different dementia knowledge and attitudes. A cross-sectional survey among 239 youth and 62 older adults using a two-step sampling approach in Macao aimed to examine the hypothesis. Results showed older adults had a higher score of dementia knowledge (F(1,299) = 45.692, p <0.001) but a lower score of dementia attitudes (F(1,299) = 161.887, p <0.001) compared to the yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Practitioners in this study had a relatively lower level of knowledge when compared with the findings of previous researches conducted in Macao. [13][14][15] The insufficient knowledge of symptoms of dementia among practitioners reflected the need for more proactive and targeted education, especially about the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners in this study had a relatively lower level of knowledge when compared with the findings of previous researches conducted in Macao. [13][14][15] The insufficient knowledge of symptoms of dementia among practitioners reflected the need for more proactive and targeted education, especially about the…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature is largely related to the knowledge of and attitudes towards dementia among healthcare professionals, students, and older adults in Macao. 13 - 15 However, building a DFC involves efforts from multiple sectors. 16 Novak et al 17 suggested that people with customer-facing roles should be highlighted in the building of DFC.…”
Section: Introductionmentioning
confidence: 99%
“…Family history and previous experiences of dementia affect not only one’s knowledge of and attitude toward dementia but also confidence in possibility of prevention (Rosenberg et al, 2020). Previous studies indicated that sufficient knowledge and positive attitude are necessary to reduce negative behaviors, suggesting that knowledge and attitudes influence behaviors (Wu et al, 2022). Fear, uncertainty and concerns over dementia is influenced by an individual’s knowledge, opinions and experiences of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…As the population continues to age, the demand for accessing healthcare including ambulance services is likely to increase. Such an increase is driven by several factors, including the growing aging population, improved awareness, early detection of dementia, the complex nature of dementia care, and the burden on caregivers of patients with dementia [13,14].…”
Section: Access To Appropriate Healthcare Servicesmentioning
confidence: 99%